A New Collective Work on Herodotus as a Scientist and Narrator - Sinitsyn, Aleksandr A.; Surikov, Igor E. (Anabasis. Studia Classica et Orientalia, 2019)
The article contains a brief description of the content and a critical analysis of a new collective monograph devoted to Herodotus: Ewen Bowie (ed.), Herodotus – Narrator, Scientist, Historian, Berlin – Boston: De Gruyter, 2018. The editors arranged all articles of this book according to topics while the concerns of most of these works cover all the three afore-mentioned subjects: Herodotus – narrator – scholar – historian. The book is an important contribution to the studies of Herodotus since it employs new historical approaches and presents novel views on the narrative and scholarly style of the historian. Moreover, the authors of each chapter put forth original arguments as to the study of both Herodotus, the main character of this book, and academic and historical and cultural context of the ancient and classic Hellas in toto, occasionally touching upon Oriental problems (first and foremost, Egyptological ones). Reviewers provide an overview of the main sections of the book, sometimes debating with the authors of the articles; the main focus is on the most significant aspects of the articles determined by the general conception of the edited volume.